GAMBARAN PENGETAHUAN DAN SIKAP MAHASISWA PROGRAM PENDIDIKAN PROFESI DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA TERHADAP “NYERI SEBAGAI TANDA VITAL KE-5” PADA TATALAKSANA NYERI AKUT DI RUMAH SAKIT PENDIDIKAN - MARSHELLA BRENDA SYAHPUTRI NASUTION; MUHAMMAD JALALUDDIN ASSUYUTHI CHALIL; ANDRI YUNAFRI; ARIL RIZALDI (JURNAL ILMIAH MAKSITEK, 2021)
In 1995 the American Pain Society (APS) instituted a campaign on "Pain as the 5th vital sign". Pain is a common reason thata person comes to the hospital seeking medical attention. The percentage of pain is higher than diabetes, heart disease andcancer. This study aims to see the level of knowledge and attitudes of P3D FK UMSU students towards pain as the 5th vitalsign in acute pain management in teaching hospitals. Using a descriptive method with a cross sectional approach, a sampleof 144 people from P3D FK UMSU students batch 2015 and 2016. The results of this study were obtained that from 94people (65.3%),out of 144 respondents had less knowledge, then 48 people (33.3%) have sufficient knowledge, and 2people (1.4%) have good knowledge.Moreover, as many as 124 people (84,4%) have a good attitude, and as many as 20people (13,6%) have bad attitude. The conclusion of this study is that P3D FK UMSU students have less knowledge andgood attitudes of pain as the 5th vital sign in acute pain management in teaching.